Biochar derived from cadmium-contaminated rice straw at various pyrolysis temperatures: Cadmium immobilization mechanisms and environmental implication. (February 2021) - Zong, Yutong; Xiao, Qing; Lu, Shenggao
Highlights: Cadmium in rice straw has a great environmental risk. Pyrolysis increased the total Cd and reduce DTPA extractable Cd content of biochars. Exchangeable Cd fraction was decreased with the pyrolysis temperature increased. Phosphate modification reduced total and DTPA extractable Cd contents in biochars. Four hypotheses were proposed to explain the mechanism of Cd immobilization in biochar. Abstract: The total concentration, chemical speciation and availability of Cd in biochar derived from Cd-contaminated rice straw were determined to evaluate the potential environmental risk of Cd in biochar and the possibility of biochar as effective way to dispose Cd-contaminated straw. The Cd was concentrated with the increased pyrolysis temperature, while the bioavailability of Cd in biochar was reduced. The sequence extraction indicated that residual fraction of Cd increased and acid exchangeable fraction decreased as pyrolysis temperature increased. The biochar modified by phosphate could significantly reduce the concentration of total and DTPA-extractable Cd in biochar. The pot experiment demonstrated that pyrolysis reduced the potential environmental risk of Cd in biochar. The precipitation and co-precipitation, physical sorption, surface electrostatic interaction, and functional group complexation could be the potential mechanisms of Cd immobilization in biochar. These findings suggested that pyrolysis would be an acceptable and feasible way to dispose contaminated rice straw.